The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00264-018-4023-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of multilevel surgery in adults with cerebral palsy

Abstract: Surgical treatment in adults with BSCP was feasible and effective in the long-term. Significant improvement of gait and function was maintained in the majority of patients, while some patients were prone to develop crouch gait, hip flexion contractures, or pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…This does demonstrate that a small number of adults, after maturity, may develop symptomatic deformities that are primarily related to planovalgus feet and hallux valgus. Although there are reports of surgical correction of gait deformities in adults with CP having a good outcome, these studies do not report if deformity onset was in adulthood or childhood 28,30. Identification of foot deformities as the major residual deformity and the deformity most likely to progress in adulthood has not been previously reported in patients with CP.…”
Section: Discussionmentioning
confidence: 94%
“…This does demonstrate that a small number of adults, after maturity, may develop symptomatic deformities that are primarily related to planovalgus feet and hallux valgus. Although there are reports of surgical correction of gait deformities in adults with CP having a good outcome, these studies do not report if deformity onset was in adulthood or childhood 28,30. Identification of foot deformities as the major residual deformity and the deformity most likely to progress in adulthood has not been previously reported in patients with CP.…”
Section: Discussionmentioning
confidence: 94%
“…37 It is thus interesting to observe that different types of procedure do not have the same impacts on long-term gait evolution. 38 In their study on long-term evolution (10.9 years) in adults (mean age at baseline: 24.8 (sd 7.6)), Putz et al 39 showed that patients with bilateral CP who underwent SEMLS had an improved gait score (GPS) over time. Thus, SEMLS is an important treatment for managing CP impairments between childhood and young adulthood, but also during the adult period.…”
Section: Discussionmentioning
confidence: 99%
“…Em geral, a m edia (DP) da percepc ßão subjetiva da marcha foi 7,5 (1,8), e foi significativamente mais alta em pacientes com Sistema de Classificac ßão da Func ßão Motora Grossa (GMFCS) n ıvel I (7,9 [1,5]) no que nos pacientes nos n ıveis GMFCS II e III (5,9 [2,0]). Correlac ßões positivas foram encontradas entre a percepc ßão subjetiva da marcha e os escores da marcha, velocidade da marcha, distância no TC6 e pontuac ßão SF-36.…”
Section: Resultsunclassified
“…These scores can be used to monitor gait quality evolution over time and after treatment. Indeed, several studies have reported post‐treatment gait outcomes (often based solely on gait quality) during childhood but with no consideration of how patients perceived their own walking abilities and capacities . However, patients’ subjective perceptions are important because they reflect how they value themselves with regards to their functional abilities, ideas of aesthetics, feelings of asymmetry, and self‐esteem .…”
mentioning
confidence: 99%
See 1 more Smart Citation